Adaptive Projective Lag Synchronization of T and Lu Chaotic Systems - Hamed Tirandaz; Mohsen Ahmadnia; Hamid Reza Tavakoli (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, the synchronization problem of T chaotic system and Lu chaotic system is studied. The parameter of the drive T chaotic system is considered unknown. An adaptive projective lag control method and also parameter estimation law are designed to achieve chaos synchronization problem between two chaotic systems. Then Lyapunov stability theorem is utilized to prove the validity of the proposed control method. After that, some numerical simulations are performed to assess the performance of the proposed method. The results show high accuracy of the proposed method in control and synchronization of chaotic systems.